A Self‐Cleaning Mucus‐like and Hierarchical Ciliary Bionic Surface for Marine Antifouling. Issue 5 (18th February 2020) - Ren, Xiaoting; Guo, Mingshuai; Xue, Lili; Zeng, Qingyang; Gao, Xianze; Xin, Yonglei; Xu, Likun; Li, Li
Abstract : The flexible mucus film and hydrophilic hierarchical micro‐/nanoprotuberance structure on the skin surfaces of marine organisms contribute to an excellent intrinsic antifouling performance. Inspired by this fact, a self‐cleaning mucus‐like and hierarchical ciliary bionic antifouling surface (SMCAS) is designed for marine antifouling based on the electrostatic flocking technology. The results of scanning electron microscopy (SEM) show that the bioinspired SMCAS has a hierarchical micro‐/nanociliary structure and the micrometer array of polyamide (PA) microfibers is covered with the nanometer carbon nanotube/polyvinyl alcohol (CNT/PVA) hydrogel particles. The biomasses of the two marine microoganisms, Nitzschia closterium f. minutissima and Marinobacter lipolyticus SM19 (T), attached on the SMCAS are investigated using a UV–visible spectrophotometer (UV–vis) and SEM. The results reveal that the microoganisms attached on the SMCAS are significantly lower number in comparison with the organic silicon coating. In addition, the SMCAS has a greater ability of stain removal in the dyed petroleum ether washing test. Therefore, the SMCAS demonstrates an extraordinary antifouling performance due to the synergetic effect of the mucus‐like hydrogel film and the hierarchical micro‐/nanostructured micropillars. Abstract : Inspired by the skin surfaces of marine organisms, a self‐cleaning mucus‐like and hierarchical ciliary bionic antifouling surface (SMCAS) is designed for marine antifouling. The results reveal that the synergetic effect of mucus‐like hydrogel film and hierarchical micro‐/nanostructured micropillars of the SMCAS leads to an extraordinary antifouling performance, which brings a new concept to the fabrication of environmental‐friendly marine antibiofouling technology.